Pengaruh Stock Split dan Kinerja Keuangan terhadap Return Saham - Hendra Hendra; Wiwit Irawati (Universitas Pamulang, 2020)
This study aims to prove empirically the effect of Stock Split and Financial Performance on Stock Return. The independent variables used in this study are Stock Split and Financial Performance, while the dependent variable is Stock Return. This research was conducted on all companies listed on the Indonesia Stock Exchange in 2015-2019 that carried out a Stock Split. The research method used is descriptive quantitative. The type of data used is secondary data in the form of published financial reports for all companies listed on the Indonesia Stock Exchange. Samples were collected by the purposive sampling method. The number of companies sampled in this study was 12 companies with a research period of 5 years so that 60 samples were obtained. Data processing using Eviews 11. Simultaneous test results show that Stock Split and Financial Performance simultaneously have an effect on Stock Returns. While the partial test results show that Stock Split partially has a significant effect on Stock Returns, Financial Performance partially has a significant effect on Stock Returns.Keywords: Stock Split, Financial Performance, Stock Return